1990
DOI: 10.1007/bf01348985
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cytomegalovirus glycoproteins in a family of complexes designated gC-II with murine monoclonal antibodies

Abstract: Several murine monoclonal antibodies (MoAbs) were made to a family of human cytomegalovirus (HCMV) disulfide linked glycoprotein complexes designated gC-II. Characterization of these MoAbs by immunological methods showed that they could be divided into two groups recognizing different glycoproteins. Western blot analysis was done with immunoaffinity purified gC-II complexes. Under non-reducing conditions MoAbs from both groups recognized gC-II complexes with molecular weights of 67-93 k and 130 k to greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The ascites was collected and screened for antibody to the peptides. The gC-II Group 1 MAbs 8B4 and 9El0 and the gC-II Group 2 MAbs 12G9, 15G5, 15F9, 27B4, 25C8, 23B10 and 40B7 used in this study were described previously (Kari et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ascites was collected and screened for antibody to the peptides. The gC-II Group 1 MAbs 8B4 and 9El0 and the gC-II Group 2 MAbs 12G9, 15G5, 15F9, 27B4, 25C8, 23B10 and 40B7 used in this study were described previously (Kari et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Group 1 MAbs recognize a glycoprotein which forms a broad band in SDS-PAGE covering Mrs of 47 000 to 63 000. Group 2 MAbs recognize glycoproteins with MrS of 48000 to 200000 (Kari et al, 1990). The glycoproteins recognized by the Group 1 and Group 2 MAbs can also be differentiated by their glycan composition.…”
Section: Introductionmentioning
confidence: 99%
“…MAbs 15F9 and 27B4 recognized gC-II disulphide-linked glycoprotein complexes and have been previously described (Karl et al, 1990a). Glycoprotein complexes containing the HCMV gB glycoprotein were immunoprecipitated with MAb 41C2 (Lussenhop et al, 1988).…”
Section: Monoclonal Antibodies (Mabs)mentioning
confidence: 99%
“…The gM/gN complex of betaherpesviruses, more specifically that of HCMV, represents the disulfide complex previously designated gCII (18). Early studies identified this disulfidelinked complex, but definitive evidence that it was composed of gM and gN has been presented only recently (25).…”
mentioning
confidence: 99%